Predictive Value of Standardized Intratumoral Metabolic Heterogeneity in Locally Advanced Cervical Cancer Treated With Chemoradiation. Issue 4 (May 2016) - Yang, Fei; Young, Lori; Grigsby, Perry
Abstract : Objective: The aim of this study was to propose and evaluate a novel image metric for quantifying spatial heterogeneity of tumor 18 F-fluorodeoxyglucose (FDG) uptake within the context of predicting response to chemoradiation in locally advanced cervical cancer. Methods: Ninety patients with locally advanced cervical cancer treated with concomitant chemoradiation were included in this study. Each patient underwent two whole-body 18 F-FDG positron emission tomography/computed tomography scans with one before the initiation of treatment for staging and the other at 12 weeks after treatment completion for response assessment. Patients were categorized in terms of response to chemoradiation into two major groups: complete metabolic responders and noncomplete metabolic responders. The capacity of the proposed intratumoral heterogeneity metric to differentiate patients with respect to response to therapy was evaluated and compared with the use of standardized uptake value indices and various texture parameters that had been previously introduced for predicting tumor response to chemoradiation. Results: At baseline, the proposed intratumoral heterogeneity metric along with four texture features, including entropy and energy derived from gray-level co-occurrence matrices and gray-level nonuniformity and zone size nonuniformity from gray-level zone size matrices, was capable of differentiating responders' groups with P values of 0.0026, 0.0252, 0.0240, 0.0234, and 0.0188, respectively. Furthermore, when compared with the texture features exhibiting significant difference between the responders' groups, the proposed metric demonstrated larger area under receiver operating characteristic curve. Conclusions: The proposed metric with quantifying spatial heterogeneity of intratumoral FDG accumulation in a normalized manner may be associated with predictive value of poor response to concurrent chemoradiation in locally advanced cervical cancer.